Corrosion and Galvanic behavior of Copper, Carbon steel and Zinc Couples in (3.5 %wt) Nacl Solution - Ali, Jamal M.; Abbas, Qasim M. (Al-Khwarizmi Engineering Journal, 2009)
The galvanic corrosion of the (Cu - Fe), (Cu - Zn) and (Fe - Zn) couples have been investigated in 3.5% NaCl solution, 40ºC, different velocities (Re = 5000, 10000 and 15000) and different area ratio’s of cathode to anode (AR= 0.5,1 and 2), by using commercial metal pipe (cylindrical tube).The Zero Resistance Ammeter has been used to measure the galvanic current (Ig) and galvanic potential (Eg) with time. The galvanic current density increases with increasing velocity (Re) and the area ratio (AR). The galvanic potential (Eg) is shifted to less negative with increasing velocity (Re) and the area ratio (AR). A statistical relations for the galvanic current density and galvanic potential as a function of (Re). and the area ratio had been created depending on Quasi-Newton method. There is good agreement between experimental and predicted results.